Conflitos ambientais no âmbito do zoneamento ecológico -econômico: o caso da gleba Nova Olinda em Santarém - Pará - Sena, Antonio Edilson de Castro (2010)
This dissertation aims at discussing environmental conflicts within the Ecological-Economic Zoning (EEZ) and the relations that this legal instrument, through the government, deals with those involved in these conflicts. The incompatibility of development projects (sentation) is the basis of environmental conflicts, and generally involves social groups suffering from an ethnic identity..The diversity expressed by these social groups is trea ted with great difficulty by the law, considering that this is guided by rules of universal application, and presuppose an abstract social uniformity. The EEZ, as an institution of this law, carries with it the difficulties in dealing with diversity and shifts the focus of this conflict to dispute over the definitions of abstract notions as "natural calling space", "production potential", "development" among others. This article is used as the reference environmental conflict occurred on Nova Olinda, a municipality of Santarém (Pará), around the definition of the destination of their areas by the Ecological and Economic Zoning of the State of Pará. This example allows us to observe how the state of Para denied recognition to the lifestyle of indigenous communities Borari- Arapiun simply ignoring them or trying to incorporate them into the initial project (and rejected by Borary-Arapiun) disposal of gleba Nova Olinda for logging. Keywords: legal pluralism, participatory community, social movements, regulatory paradigm.